Preparing small and medium enterprise businesses for post-COVID-19: lean management approach / Azyyati Anuar ... [et al.] - Anuar, Azyyati; Sadek, Daing Maruak; Che Mamat, Rusalbiah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The spread of Covid-19 pandemic in Malaysia was confirmed on January 25th, 2020 (Bernama, 2020). As the virus spread in all states and federal territories in Malaysia, in March 16th, the Malaysian government has enforced a partial nationwide curfew (known as the Movement Control Order or MCO) from March 18th to June 9th, 2020 to curb the increasing number of positive cases in the country (Bernama, 2020). Consequently, the effects of Covid-19 have disrupted the economy, not only in Malaysia but also globally. The post-Covid-19 world economy is expected to bring down the global Gross Domestic Product (GDP) to 0.4 per cent from its initial forecast of US 86.6 trillion for 2019. This loss counts for the global economic loss of US 3.5 trillion (Bernama, 2020a).